Perkembangan Tradisi Keilmuan Islam dan Gerakan Pemikiran: Islam Madzhab Ciputat dan Himpunan Mahasiswa Islam - Samudra Eka Cipta; Taufan Sopyan Riyadi (Universitas Muhammadiyah Magelang, 2020)
The 1980s is an important part of Indonesia’s history of Islamic Student Movement. It is known as a period that marked the beginning of the rise of thought among academics. During this period, IAIN Jakarta became the epicenter of the development of the Islamic thought movement. Many prominent scholars such as Azyumardi Azra, Harun Nasution, Nurcholis Madjid, and other figures were mobilized and they became collectively known as the Ciputat Islamic School. This paper used the method of historical and literature studies. The research concludes that the Ciputat School is not a school or a belief but rather a reforming movement of Islamic thought among Muslim academics which is inseparable from the existence of the Islamic Student Association in the past.